2016
DOI: 10.1186/s12884-016-1000-2
|View full text |Cite
|
Sign up to set email alerts
|

Uterine salvage management for atonic postpartum hemorrhage using “modified lynch suture”

Abstract: BackgroundTo assess the effectiveness of the new modified technique in order to control bleeding in women presenting with atonic, flabby uterus compared to the most commonly described technique of classic B-Lynch suture.MethodThis study included 160 women of uncontrolled atonic postpartum hemorrhage delivered by cesarean section at Ain Shams University Maternity Hospital between January 2013 and October 2015. Participants were randomly assigned following simple randomization procedures (computerized random num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…3C). 21,35 El-Sokkary et al 22 have published another variation: it begins on the anterior aspect of the uterus below the hysterotomy, but the thread, after exiting above the hysterotomy, crosses the uterine fundus on the contralateral side and is inserted in the posterior wall on that same side. On the posterior aspect of the uterus the suture is performed as B-Lynch description but on the anterior wall the thread crosses again creating an X-shaped suture.…”
Section: Types Of Uterine Compression Suturesmentioning
confidence: 99%
See 2 more Smart Citations
“…3C). 21,35 El-Sokkary et al 22 have published another variation: it begins on the anterior aspect of the uterus below the hysterotomy, but the thread, after exiting above the hysterotomy, crosses the uterine fundus on the contralateral side and is inserted in the posterior wall on that same side. On the posterior aspect of the uterus the suture is performed as B-Lynch description but on the anterior wall the thread crosses again creating an X-shaped suture.…”
Section: Types Of Uterine Compression Suturesmentioning
confidence: 99%
“…On the posterior aspect of the uterus the suture is performed as B-Lynch description but on the anterior wall the thread crosses again creating an X-shaped suture. 22 The association of B-Lynch suture with other postpartum haemorrhage control techniques have also been described. Nelson and O'Brien 29 have reported five cases in which B-Lynch's compression sutures were performed but were not successful, so they've applied an intrauterine Bakri balloon -'uterine sandwich technique'.…”
Section: Types Of Uterine Compression Suturesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is close to the study done by ElSokkary et al in Cairo, Egypt where they found that the mean age was 29.3 years. 12 Similarly, Nalini et al reported 28 years mean age. 13 On the contrary, Koh et al reported 35 years as the mean age 14 , which can be explained by elderly gravid uterus leading to atonicity and thus PPH.…”
Section: Discussionmentioning
confidence: 99%
“…Since its creation, several authors have described modifications to the original technique; however, all handle the same concept, that is, uterine compression [27,28].…”
Section: Prolonged Labormentioning
confidence: 99%